Key Drivers of Live Streaming Adoption: An Empirical Analysis Using the UTAUT Model - Oktaviani, Retno Fuji (Jurnal Aplikasi Manajemen, 2025)
This study is important considering the rapid adoption of live streaming technology in the fashion industry, which has become a primary tool for boosting sales. Understanding the factors influencing fashion vendors' use of this technology is crucial, as it can help businesses and marketplace platforms design more effective and interactive marketing strategies. This study examines how behavioral intention affects the actual use of live streaming technology, while also considering the moderating role of gender in the relationships between these variables. The study adopts a quantitative approach, collecting data through a questionnaire survey. The population for this study consists of fashion vendors who actively use live streaming features on marketplaces such as Shopee, Tokopedia, and Lazada in the Tanah Abang area. Purposive sampling was employed as the sampling technique, as the study requires fashion vendors who meet specific criteria, namely, those who have used live streaming technology to sell their products on marketplaces. As a result, the sample size amounted to 211 participants. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software to test the model’s validity and the relationships between variables. The findings show that trust significantly affects performance expectancy and effort expectancy. Both performance expectancy and effort expectancy significantly influence behavioral intention, and behavioral intention, in turn, positively affects the actual use of live streaming. This study offers new insights into how gender differences influence fashion vendors' perceptions and decisions when using live streaming technology as a marketing tool. Furthermore, it provides a deeper understanding of how trust in technology can strengthen performance and effort expectancies, ultimately enhancing behavioral intention and the actual use of live streaming technology.